Global e-learning: a phenomenological study - Rao, Sudendra R., author; Quick, Don, advisor; Banning, Jim, committee member; Venneberg, Don, committee member; Athey, Susan, committee member (Colorado State University. Libraries, 2011)
There is a strong sense that the educational processes must change, if for no other reason than to keep up with a rapidly emerging information-based society. As the need for learning and knowledge has outstripped what is possible using conventional learning methods, e-Learning may allow us to respond more effectively. The new generations of e-Learning technologies that allow interactive knowledge construction and provide richer learning environments have been gaining increased global acceptance. This qualitative study with an interpretative phenomenological approach indicated the evolution, current status and anticipated future advances of e-Learning among academia, corporations and the governments across developed and developing countries. The data was collected through in-depth interviews with subject matter experts. With e-Learning interventions rapidly becoming organization's response to continuous learning and change in the new economy, this study provided evidence that e-Learning is a growing global phenomenon and if the potential is turned into reality, e-Learning will be transformative. The shortening product development cycle, lack of skilled workforce, increasing global competition and a shift from the industrial to the knowledge economy and the fast-paced advances with the related technology, e-Learning is here to stay and could be the answer to tomorrow's learning needs.
Keywords: global e-learning